Identifying the social dominance order in a mixed breed herd: A practical methodology - Landaeta Hernández, Antonio; Chenoweth, Peter; Randles, Ronald; Littell, Ramon; Rae, Owen; Chase, Chad (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The major objective of this study was to identify a simple and accurate method of assessing differences in female social status. Three methods of estimating dominance value (DV) were compared in beef cows of three breed-types; Angus (A; n=10), Brahman (B; n=10), and Senepol (S; n=10). Cows were equitably assigned to two groups of fifteen each, allocated into separate pastures and containing equal number of animals by breed. Agonistic interactions were recorded for 45 d of study, in two 1 h periods during concentrate feeding using the method of competitive orders winner/loser. Methods of estimating DV included: I) Ratio between individuals dominated and total encountered, II) Ratio between encounters won to total encounters, III) Proportion of individuals dominated to total herdmates. Due to the different level of interactivity evidenced among animals as well as between and within social orders, method III with subsequent arc-sin transformation was considered as the most practical and accurate method for estimating DV and subsequent allocation of cows into a social dominance order. In addition, a breed effect was found on social dominance. Senepol cows obtained greater DVÂ´s (1.24 Ó 0.08) than Angus (0.97 Ó 0.08; P < 0.03) and Brahman cows (0.76 Ó 0.08; P < 0.005).